The Effect of Metformin in Experimentally Induced Animal Models of Epileptic Seizure - Ebrahim M. Yimer; Awol Surur; Dawit Zewdu Wondafrash; Abadi Kahsu Gebre (Behavioural Neurology)
Background. Epilepsy is one of the common neurological illnesses which affects millions of individuals globally. Although the majority of epileptic patients have a good response for the currently available antiepileptic drugs (AEDs), about 30-40% of epileptic patients are developing resistance. In addition to low safety profiles of most of existing AEDs, there is no AED available for curative or disease-modifying actions for epilepsy so far. Objectives. This systematic review is intended to evaluate the effect of metformin in acute and chronic animal models of an epileptic seizure. Methods. We searched PubMed, SCOPUS, Sciences Direct, and grey literature in order to explore articles published in English from January 2010 to November 2018, using key terms “epilepsy,” “seizure,” “metformin,” “oral hypoglycemic agents,” and “oral antidiabetic drugs”. The qualities of all the included articles were assessed according to the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES). Results. Out of six hundred fifty original articles retrieved, eleven of them fulfilled the inclusion criteria and were included for final qualitative analysis. In these studies, metformin showed to control seizure attacks by attenuating seizure generation, delaying the onset of epilepsy, reducing hippocampal neuronal loss, and averting cognitive impairments in both acute and chronic models of an epileptic seizure. The possible mechanisms for its antiseizure or antiepileptic action might be due to activation of AMPK, antiapoptotic, antineuroinflammatory, and antioxidant properties, which possibly modify disease progression through affecting epileptogenesis. Conclusion. This review revealed the benefits of metformin in alleviating symptoms of epileptic seizure and modifying different cellular and molecular changes that affect the natural history of the disease in addition to its good safety profile.